Proteomics and metabolomics analyses of mechanism underlying bovine sperm cryoinjury - Renzheng Zhang; Xiuyuan Wang; Ruili Liu; Yanfang Mei; Xiuping Miao; Jiaxu Ma; Lei Zou; Qiuyue Zhao; Xuejin Bai; Yajuan Dong (BMC Genomics)
Abstract Background The cryoinjury of semen during cryopreservation reduces sperm motility, constraining the application of artificial insemination (AI) in bovine reproduction. Some fertility markers, related to sperm motility before and after freezing have been identified. However, little is known about the biological mechanism through which freezing reduces sperm motility. This study investigated the selective effects of cryoinjury on high-motility sperm (HMS) and low-motility sperm (LMS) in frozen-thawed from the perspectives of reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and ATP levels. The molecular mechanism of decreased sperm motility caused by cryoinjury was explored through a joint analysis of 4D-label free quantitative proteomics and non-targeted metabolomics. Results The results indicate that low levels of ROS and high degrees of MMP and ATP play a critical role in the survival of HMS during the freezing process. The sperm samples from the frozen-thawed HMS and LMS were analysed for proteomics and metabolomics, 2,465 proteins and 4,135 metabolites were detected in bovine sperm samples. In contrast to LMS, HMS have 106 proteins and 106 metabolites with high abundance expression, and 79 proteins and 223 metabolites with low abundance expression. Proteomics and metabolomics data exhibit that highly expressed antioxidant enzymes and metabolites in HMS can maintain sperm motility by regulating the ROS produced during freezing to prevent sperm from oxidative stress and apoptosis. Furthermore, the KEGG analysis of differential proteins and metabolites during the freezing process implies that the significant enrichment of glycolysis and cAMP in HMS can guarantee energy supply. Conclusions The results provided that during the process of bovine sperm freezing, highly expressed antioxidant enzymes can regulate the reactive oxygen species levels to avoid oxidative stress and the glycolysis signalling pathway ensures ATP production can sustain frozen-thawed sperm motility.